Bank Loan Financing for Small and Medium Enterprise: Interactive Game Industry Player Perspective - Dhewanto, Wawan; Herliana, Sri; Fadhil, Ilham; Lawiyah, Nur (SBM ITB, 2019)
Abstract. The interactive game sector is one of the promising industries in Indonesia. Indonesia is a developing country, where the creative industry sector in the application and game developer fields is growing well. This developing industry needs supporting infrastructure such as financing and human capital supply. Companies need financing for their operations, marketing, and business expansion. Various funding sources are available for companies such as venture capital, bank loan, personal savings, and liability certificates. Bank loan, a form of conventional financing has its own advantages to support the interactive game industry. On the other hand, the capital structure of interactive game SMEs (small and medium enterprises) holds a small portion of loans, especially bank loan. This study aims to analyze the role of financing support, especially bank loan support for the Indonesian interactive gaming SMEs. The results of the study show that bank loan, although less favored, has the potential to engage more deeply in the interactive gaming industry environment. The study also shows that this type of business has not been maximally touched by banks in financial support. Furthermore, the results show that SMEs that are still in the early stages are more likely to focus on human resources than financial resources. Nevertheless, they still need financial support in several aspects of business development, although not necessary from the support of bank loan.Keywords: Financing, interactive game company, bank loan, small and medium enterprise, Indonesia Abstrak. Sektor permainan interaktif adalah salah satu industri yang menjanjikan di Indonesia. Indonesia sendiri merupakan negara berkembang, dimana sektor industri kreatif di bidang aplikasi dan game developer sedang berkembang baik. Industri yang sedang berkembang ini membutuhkan infrastruktur pendukung seperti pembiayaan, dan pasokan modal manusia. Perusahaan membutuhkan pembiayaan untuk operasi mereka, pemasaran dan ekspansi bisnis. Berbagai sumber pendanaan tersedia untuk perusahaan seperti modal ventura, pinjaman bank, tabungan pribadi, dan sertifikat obligasi. Pinjaman bank, bentuk pembiayaan konvensional memiliki kelebihan sendiri untuk mendukung industri permainan interaktif. Di sisi lain, struktur permodalan UKM (usaha kecil dan menengah) permainan interaktif memegang porsi kecil untuk pinjaman, terutama pinjaman bank. Penelitian ini bertujuan untuk menganalisa peranan dukungan finansial untuk UKM game interaktif, dalam hal ini adalah dukungan pinjaman bank. Hasil penelitian menunjukkan bahwa pinjaman bank meskipun kurang disukai, memiliki potensi untuk terlibat lebih dalam di lingkungan industri game interaktif. Dari sisi bank pun menunjukkan bahwa jenis bisnis ini belum maksimal tersentuh oleh bank dalam dukungan keuangan. Hasil lain juga menunjukkan bahwa UKM yang masih berada di tahap awal usaha lebih cenderung fokus pada sumber daya manusia dibandingkan sumber daya keuangan. Meskipun demikian mereka tetap membutuhkan dukungan keuangan dalam beberapa aspek pengembangan usaha.Kata kunci: Pembiayaan, perusahaan game interaktif, pinjaman bank, usaha kecil dan menengah, Indonesia